2017
DOI: 10.4172/2155-9600.1000584
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Composition of Quail Meatballs and Quail Pickled Eggs

Abstract: The aims of this study were to evaluate the acceptance of meatballs and pickled quail eggs, determine the nutritional composition of the quail pickled eggs and quail meatballs. Data indicate that quail meatballs and pickled quail eggs are an acceptable market product. The quail meatballs have 70.56% moisture content and 29.44% dry matter which include 7.78%, 12.98%, 7.10% and 2.48% in wet basis for total lipids, proteins, ash and carbohydrate, respectively. Total cholesterol content in quail meatballs was 0.08… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…A quail egg is an excellent source of nutrients (Table 3 ) such as protein, lipids, vitamins (A, C, D and B complex) and minerals as well as other substances such as lysozymes, ovomucoid and cystatin that have therapeutic effects [ 12 , 13 ]. The protein quality of a quail egg is characterised by high leucine, lysine, and valine contents [ 12 , 42 ], which are required for normal functioning of the body. For example, lysine is required to produce antibodies, hormones and enzymes as well as assisting in calcium absorption [ 32 ].…”
Section: An Overview Of the Nutritional Benefits Of Quail Productsmentioning
confidence: 99%
“…A quail egg is an excellent source of nutrients (Table 3 ) such as protein, lipids, vitamins (A, C, D and B complex) and minerals as well as other substances such as lysozymes, ovomucoid and cystatin that have therapeutic effects [ 12 , 13 ]. The protein quality of a quail egg is characterised by high leucine, lysine, and valine contents [ 12 , 42 ], which are required for normal functioning of the body. For example, lysine is required to produce antibodies, hormones and enzymes as well as assisting in calcium absorption [ 32 ].…”
Section: An Overview Of the Nutritional Benefits Of Quail Productsmentioning
confidence: 99%
“…As the demand for animal protein rises, quail breeding is seen as an alternative method for meat production, competing with broilers as a protein source. Quail meat and eggs are rich in vitamin E, protein, minerals, fat, and hormones, making them a healthy dietary option that can help people in developing countries who lack some or all of the necessary nutrients for optimal health (Bayomy et al 2017). Furthermore, quail meat surpasses chicken in terms of protein content.…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional value is one of the factors that increases the demand for quail eggs worldwide. Studies have reported that quail eggs contain essential nutrients, which play a vital role in human health and in disease prevention and curing (Bayomy et al, 2017;Tunsaringkarn et al, 2012). In addition, quail egg carries good quality characteristics that could positively influence the acceptability of consumers (Yannakopoulos, and Tserveni-Gousi, 1986).…”
Section: Introductionmentioning
confidence: 99%